1999
DOI: 10.4269/ajtmh.1999.60.165
|View full text |Cite
|
Sign up to set email alerts
|

Fecal occult blood testing on Trichuris-infected primary school children in northeastern peninsular Malaysia.

Abstract: Abstract. Stool specimens of 104 primary schoolchildren (mean Ϯ SD age ϭ 8.2 Ϯ 0.3 years) were examined for helminth eggs and for occult blood to investigate the possibility that trichuriasis causes occult intestinal bleeding in the absence of the overt Trichuris dysentery syndrome. A commercially available guaiac test was used to detect fecal occult blood. Sixty-one children had Trichuris infection, 11 of whom had heavy infections (Ͼ 10,000 eggs per gram of feces [epg]), and 53 had Ascaris infections. No hook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…This was caused by occult blood loss from colonic lesions. 17 This blood loss presumably was caused by mucosal petechial lesions, and blotchy mucosal hemorrhages were caused by burrowing of the anterior end of the worm into the mucosa. As expected, there was no effect on the nutritional status of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was caused by occult blood loss from colonic lesions. 17 This blood loss presumably was caused by mucosal petechial lesions, and blotchy mucosal hemorrhages were caused by burrowing of the anterior end of the worm into the mucosa. As expected, there was no effect on the nutritional status of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies illustrated that occult blood is not correlated with T. trichiura infection, unless there is a Trichuris dysentery syndrome (TDS) [6, 7, 10]. Similarly for hookworms, they do not lead to a significant occult gastrointestinal bleeding unless high-burden infection occurs [11–13].…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms of trichuris-related anemia include worm consumption of blood in the context of heavy infections, colonic lesions with associated bleeding, or chronic reduction in food and micronutrient intake due to the anorexia inducing effects of TNF-alpha released in response to infection [86, 89]. Of note, one study assessing occult blood loss with T. trichiura found that trichuriasis does not lead to significant occult gastrointestinal bleeding in the absence of TDS [90]. …”
Section: Trichurismentioning
confidence: 99%